2018
DOI: 10.1038/s10038-018-0494-z
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of genome cohort participants’ genetic knowledge and preferences to receive genetic results before and after a genetics workshop

Abstract: Several biobanks have begun returning genetic results to individuals, making the development of public genetic literacy an urgent task for their effective use. No research exists regarding the effects of genetic education on biobank participants, so we conducted genetics workshops with specialists, and surveyed differences in the participants' (n = 112) preferences to receive their own genetic information by disease categories and their genetic knowledge using questionnaires before and after the workshops. Alm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 14 publications
2
10
0
Order By: Relevance
“…In a sample of individuals diagnosed with major depression, bipolar disorder, schizophrenia, or anxiety disorder, more participants were interested in psychiatric genetic testing if effective treatment existed (Laegsgaard et al, 2009). This finding parallels results from other studies focused on common diseases (Murphy et al, 2008;Yamamoto et al, 2018) which show that most people are more interested in receiving genetic feedback for treatable or actionable conditions and less interested in feedback for conditions where there were no prevention or treatment programs (Murphy et al, 2008).…”
Section: Effective Treatment For Conditionsupporting
confidence: 72%
“…In a sample of individuals diagnosed with major depression, bipolar disorder, schizophrenia, or anxiety disorder, more participants were interested in psychiatric genetic testing if effective treatment existed (Laegsgaard et al, 2009). This finding parallels results from other studies focused on common diseases (Murphy et al, 2008;Yamamoto et al, 2018) which show that most people are more interested in receiving genetic feedback for treatable or actionable conditions and less interested in feedback for conditions where there were no prevention or treatment programs (Murphy et al, 2008).…”
Section: Effective Treatment For Conditionsupporting
confidence: 72%
“…Interest was highest for diseases that could be modified by lifestyle, as well as adult-onset and actionable conditions, with much less interest expressed in receiving pharmacogenetics and adult-onset non-actionable results [ 41 ]. Yet, a second Japanese study conducted an educational workshop with 112 participants and showed that scores for interest in receiving five categories of results–lifestyle diseases, pharmacogenetics, adult-onset non-clinically actionable diseases, non-clinically actionable multifactorial diseases, and all genetic information–significantly decreased after the workshop [ 114 ]. However, even in the face of this decrease, over 95% still wanted to know results for the diseases that could be influenced by lifestyle, pharmacogenetics, and adult-onset clinically actionable diseases [ 114 ].…”
Section: Views On Return Of Study-specific Resultsmentioning
confidence: 99%
“…Yet, a second Japanese study conducted an educational workshop with 112 participants and showed that scores for interest in receiving five categories of results–lifestyle diseases, pharmacogenetics, adult-onset non-clinically actionable diseases, non-clinically actionable multifactorial diseases, and all genetic information–significantly decreased after the workshop [ 114 ]. However, even in the face of this decrease, over 95% still wanted to know results for the diseases that could be influenced by lifestyle, pharmacogenetics, and adult-onset clinically actionable diseases [ 114 ]. In addition, 17 parents of healthy children participating in a biobank wanted to know both childhood- and adult-onset medically actionable conditions for their child and felt it was more important to protect their child’s health than preserve their future autonomy [ 115 ].…”
Section: Views On Return Of Study-specific Resultsmentioning
confidence: 99%
“…The findings of our study suggest the importance of utilizing approaches to enhance familiarity with genetics/ genomics and address various privacy concerns to improve mothers' acceptance of genetic analysis. Educational activities such as workshops may be effective in increasing participants' understanding [35]. However, face-to-face recontact with participants is quite difficult in a longitudinal large-scale cohort study.…”
Section: Discussionmentioning
confidence: 99%